Morphometric study of the structure of rat kidneys during the first hour of exposure to Leiurus macroctenus scorpion venom - Matkivska, R.M. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. Pathogens of external origin, entering the human body by various routes, can disrupt the typical structure of the kidneys and cause significant functional disorders. The degree of morphological changes depends on the strength, concentration and duration of exposure to the stimulus. Toxic compounds in animal venoms penetrate the victim’s body and disrupt the stability of the internal environment. The primary mechanisms of pathological changes are linked to alterations in cellular structure, function, and the progression of biochemical reactions. During evolution, toxins have developed strategies for penetrating target organs, which leads to numerous pathological changes. Objective. Study of morphometric data of the structure of rat kidneys during the first hour of exposure to Leiurus macroctenus scorpion venom. Methods. The study used 10 white male laboratory rats weighing 200 g (±10 g), grown in the vivarium of the Educational and Scientific Centre "Institute of Biology and Medicine" of Taras Shevchenko National University of Kyiv. The venom of scorpions of the species Leiurus macroctenus was administered to rats once intramuscularly (0.5 ml of venom solution previously dissolved in saline; 28.8 μg/ml; LD50=0.08 mg/kg). Morphometric studies were conducted using the SEO ImageLabBio, ImageJ, and STATISTICA 10.0 programs. The studies were conducted at the specified experimental periods in preparations stained with hematoxylin and eosin. Arithmetic means (M), errors of arithmetic means (m), coefficients of variation, and standard deviations were calculated. Changes were considered significant at p≤0.05. Results and conclusion. When a scorpion stings, after 1 hour, toxic substances cause the onset of substantial hemodynamic disorders and the initiation of inflammatory processes in the organ, acute renal failure as a result of acute damage to the glomerular apparatus, which is confirmed by a statistically significant increase in their parameters. Intracellular oedema and epithelial dystrophy lead to a substantial increase in the morphometric parameters of the organ’s tubules.